2022
DOI: 10.1080/08897077.2022.2074605
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of People with Substance use or Mental Health Disorders in the US

Abstract: Background: Caregiving for persons with substance use and/or mental health disorders (SU/MHD) and other conditions places significant strains on caregivers. Methods: The present study used Behavioral Risk Factor Surveillance System (a US health survey) data to (1) compare caregivers of recipients with SU/MHD to those of recipients with other conditions on demographic and caregiving characteristics and health outcomes and (2) examine demographic and caregiving characteristics that were associated with poorer he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Numerous academic studies have explored the correlation between caregiving responsibilities and the subsequent impact on the mental well-being of caregivers, thereby furnishing substantiating evidence in favor of this assertion. Previous studies have indicated that individuals who provide care for those with mental disorders, such as schizophrenia, bipolar affective disorder, and substance use disorder, tend to exhibit elevated levels of depressive and anxiety symptoms [57][58][59][60]. The combination of the responsibility of providing care and the societal disapproval linked to specific mental disorders can lead to heightened depressive symptoms among individuals who assume the role of caregivers [61].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous academic studies have explored the correlation between caregiving responsibilities and the subsequent impact on the mental well-being of caregivers, thereby furnishing substantiating evidence in favor of this assertion. Previous studies have indicated that individuals who provide care for those with mental disorders, such as schizophrenia, bipolar affective disorder, and substance use disorder, tend to exhibit elevated levels of depressive and anxiety symptoms [57][58][59][60]. The combination of the responsibility of providing care and the societal disapproval linked to specific mental disorders can lead to heightened depressive symptoms among individuals who assume the role of caregivers [61].…”
Section: Discussionmentioning
confidence: 99%
“…These statements were typically endorsed by support people but rejected by professionals and people with lived experience. This discrepancy potentially highlights the lack of support and pressure placed on support people affected by substance use problems, as well as the impact of ongoing substance use problems on support people [ 30 ].…”
Section: Discussionmentioning
confidence: 99%